Evaluación de tres abonos orgánicos (estiércol de bovino, cuyaza y humus), con dos dosis de aplicación en el cultivo de cebolla perla (Allium cepa), en el sector de Salache. Latacunga. Cotopaxi. 2021 - Cuchiparte Umajinga, Claudio David (2021)
This research aimed to evaluate the effect of three organic fertilizers (bovine manure, guinea pig manure, and humus), with two application doses in the pearl onion (Allium cepa) cultivation, at the Technical University of Cotopaxi, Salache sector. The specific objectives of the research were: Identify the best fertilizer and the best application dose in the production of pearl onion (Allium cepa) and Analyze the influence of organic fertilizers on the chemical properties of the soil. The experiment was conducted in a randomized complete block design (RCBD) with three repetitions, with a 3 x 2 + 1 factorial arrangement. The variables evaluated were: number of leaves, plant height, bulb diameter, and bulb weight. The research expressed the following results: in plant height, treatment T2 (50 t / ha of bovine manure) reached the first places in averages at 60 days with 30.93 cm; 80 days at 43.90 cm; 100 days with 52.90 cm, and 126 days with 56.78 cm; regarding the number of leaves, the same treatment obtained at 126 days an average of 8 leaves; concerning the diameter and weight of the bulb, treatment T1 (25 t / ha of bovine manure) obtained 5.37 cm and 129.58 g, respectively. Regarding the analysis of the chemical properties of the soil, the results of the investigation revealed that applying organic fertilizers such as (bovine manure, guineapig manure, and humus) at different doses; from 25 t / ha, 50 t / ha significantly increased the percentage of micro and macronutrient (NPK) in the final soil analysis, the percentage of organic matter increased from 1% at the beginning to 1.80% at the end with the manure of bovine, pH decreased from 10.14 to 9.31. Consequently, bovine manure is a alternative for pearl onion cultivation and recovery of eroded soils in Salache.